Review of G. Ilčiukienė’s Monograph “Muzikos poveikis mokant anglų kalbos pradiniame etape” - Gledhill, John R. M. (Taikomoji kalbotyra, 2012)
Dr Ilčiukienė’s monograph argues convincingly for placing music at centre of L2 language curriculum in the Lithuanian primary school in face of the fact that music has up to the present time been treated as an ancillary classroom activity in the L2 primary classroom in Lithuania. (This is also the case in most European L2 primary curricula such as in Britain and Germany where the musical activities are usually confined to the status of an optional extra and, at most, are regarded as an effective form of consolidation of material covered in any particular language input unit in a course book.) Ilčiukienė’s argumentation demonstrates not only that music motivates learners by providing a more relaxing and enjoyable classroom atmosphere (positive affect) and that the prosodic features music can provide an excellent basis for acquiring English intonation but also that music can even facilitate the acquisition of syntax, idiom and lexis. For these reasons alone, music should acquire a new status in L2 primary courses.